Dense pair plasma generation by two laser pulses colliding in a cylinder channel - 刘建勋 马燕云 余同普 赵军 杨晓虎 邹德滨 张国博 赵媛 杨靖康 李汉臻 卓红斌 邵福球 Shigeo Kawata (Chinese physics B, 2017)
An all-optical scheme for high-density pair plasmas generation is proposed by two laser pulses colliding in a cylinder channel. Two dimensional particle-in-cell simulations show that, when the first laser pulse propagates in the cylinder, electrons are extracted out of the cylinder inner wall and accelerated to high energies. These energetic electrons later run into the second counter-propagating laser pulse, radiating a large amount of high-energy gamma photons via the Compton back-scattering process. The emitted gamma photons then collide with the second laser pulse to initiate the Breit-Wheeler process for pairs production. Due to the strong self-generated fields in the cylinder, positrons are confined in the channel to form dense pair plasmas. Totally, the maximum density of pair plasmas can be 4.60 × 10^27 m%-3, for lasers with an intensity of 4 × 10^22 W.cm^-2. Both the positron yield and density are tunable by changing the cylinder radius and the laser parameters. The generated dense pair plasmas can further facilitate investigations related to astrophysics and particle physics.